PEMBELAJARAN ENGLISH PUBLIC SPEAKING BERBASIS PROJECT-BASED LEARNING - Difiani Apriyanti; Sumira Sumira; Sariani Sariani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
Learning Public Speaking does not only include good speaking English but also gives attractive performance. However, this is not easy due to the fearness and anxiety with various symptoms such as a rapid heartbeat, wet palms, or vibrating sounds. In order to minimize the obstacles, Project Based Learning (PBL) is designed. The students are assigned to be public speakesr sharing the information about agency programs to public. The project was eventually documented in the form of videos. To find out the success of the learning, a qualitative descriptive study was conducted on the video project. The subject of the research was a female student whose public speaking videos were analyzed. The sample was selected purposively because women have greater public speaking anxiety than men do. As the result, at first, the students did not have problems in making the text (content) to be presented, but it was problematic in the delivery. The first video shows public speaking fear that has not been resolved so that delivery occurs at a low level. Secondly, while in the second video it shows self confidence resulting a high delivery capability. It can be concluded that having one real experience as a public speaker makes the student able to overcome public speaking fear or anxiety.